2009
DOI: 10.1016/j.febslet.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Bag‐1M inhibits the transactivation of the glucocorticoid receptor via recruitment of corepressors

Abstract: a b s t r a c tThe Bcl-2 associated athanogene 1M (Bag-1M) is known to repress the transactivation of the glucocorticoid receptor (GR). We report here that Bag-1M inhibits the action of GR via recruitment of corepressors, including nuclear receptor corepressor (NcoR) and silencing mediator for retinoic acid and thyroid hormone receptor (SMRT), and histone deacetylase (HDAC)3 to the genomic response element of a glucocorticoid-regulated human metallothionein IIa (hMTIIa) gene. A mutant GR lacking the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…While such associations have been documented, we believe this work to be the first to demonstrate interactions among all three proteins, GR, SMRT, and HDAC1, and also the first to demonstrate such in natural killer cells. Others have shown that GR interacts with HDAC2 [36] and HDAC3 [37], as well as NCoR [37]. Contrary to those studies, these data demonstrate that GR does not appear to interact with NCoR, HDACs 2 or 3 in YT-Indy cells during Dex treatment.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…While such associations have been documented, we believe this work to be the first to demonstrate interactions among all three proteins, GR, SMRT, and HDAC1, and also the first to demonstrate such in natural killer cells. Others have shown that GR interacts with HDAC2 [36] and HDAC3 [37], as well as NCoR [37]. Contrary to those studies, these data demonstrate that GR does not appear to interact with NCoR, HDACs 2 or 3 in YT-Indy cells during Dex treatment.…”
Section: Discussioncontrasting
confidence: 78%
“…As GR has been shown to interact with both NCoR and SMRT [37], the preference for one corepressor over the other may be due to differences in the subcellular environment among different cell types. Interaction between hormone nuclear receptors like GR and corepressors depend on a number of factors, including the direct binding between GR and the corepressor’s interacting domains, as well as the composition of the corepressor complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first evidence that BAG-1 occupies the gene promoter of a key growth regulatory cytokine, although it is likely that the regulation of TGFB1 gene expression involves BAG-1 as part of a multi-protein complex. For example, recent data identified BAG-1 as part of a trimeric complex [44], where glucocorticoid-mediated transcription was regulated by BAG-1 mediated recruitment of co-repressors [45]. Interestingly, a previous study has shown TGFB1 expression to be modulated by the p65 subunit of NF-κB [46] and BAG-1 has recently been identified as a regulator of NF-κB signalling [12,22].…”
Section: Discussionmentioning
confidence: 99%
“…BAG-1 proteins are co-chaperones that are involved in the regulation of SHRs. Different BAG-1 proteins exert varying effects on SHRs, ranging from inhibition, as shown for GR, to enhancement of the transactivation function [50] . In PCa, BAG-1 is often overexpressed and enhances AR activity [39] .…”
Section: Co-chaperones Of Armentioning
confidence: 99%